Fabricating transdermal film formulations of montelukast sodium with improved chemical stability and extended drug release. Issue 3 (March 2023) - Aashli,; Reddy, S. Giridhar; Siva Kumar, B.; Prashanthi, K.; Murthy, H.C. Ananda
Abstract: Montelukast Sodium (MK) is a leukotriene receptor antagonist, an oral drug generally prescribed to control chronic asthma symptoms. This research aims to provide the transdermal delivery of this drug in a controlled release profile as a better mode of drug delivery, specifically for the pediatric and elderly population. Transdermal delivery of the drug not only improves the drug's bioavailability but also maintains the concentration of the drug in the plasma without increasing the frequency of the drug dosage. Transdermal film formulations were developed using sodium alginate (SA) and lignosulphonic acid (LS) as the matrix and PEG-400 or Glycerine (Gly) as the plasticizers. Various physiochemical characteristic evaluations of the formulated films were conducted, revealing that the formulation with Glycerine as the plasticizer had a smooth surface and was flexible. It was observed that this formulation had the highest moisture uptake capacity and the lowest moisture loss capacity when compared with the other two formulations. It was also observed that the barium chloride cross-linked formulation had a higher swelling index when compared with calcium chloride cross-linked films. The surface pH of all the formulations was monitored to be around 7.5. In the in vitro release studies, the cross-linked films showed a controlled release over 36 h compared with the non-cross-linked films. Based on the observations and results, the cross-linked film formulation showed a better-controlled release of the drug and could potentially increase its bioavailability. TGA analysis of the polymeric mixture demonstrated the thermal stability of the SA blends, which enhanced the flexibility of the SALS blend with Glycerine. XRD of samples confirmed the amorphous nature of SALS blends with Gly, which influences the flexibility of the blend. The blends are further investigated for morphology using SEM to test their compatibility with the drug.